RADIOCARBON DATING OF CHARCOALS FROM HISTORICAL MORTARS FROM TÝŘOV AND PYŠOLEC CASTLES. Issue 9 (22nd August 2022) - Pachnerová Brabcová, Kateřina; Krofta, Tomáš; Valášek, Vojtěch; Suchý, Václav; Kundrát, Pavel; Šimek, Pavel; Kozlovcev, Petr; Kotková, Kristýna; Fialová, Anna; Povinec, Pavel P; Válek, Jan; Světlík, Ivo
Abstract: Organic inclusions in lime binders provide useful samples for radiocarbon dating of historical objects. Two Czech castles Týřov and Pyšolec from Late Middle Ages were explored, and tens of charcoals were found in their walls. The radiocarbon content of the charcoals was measured with accelerator mass spectrometry. The dating results showed that none of the charcoals were younger than the known historical ages (Týřov: 1260 - 1270, Pyšolec: 1300 - 1340), but some were considerably older. Two charcoals from Pyšolec castle dated to Palaeolithic, likely originating from fluvial sediments added as an aggregate to the mortar. When excluding these two charcoals, the others indicated most likely dates being 50–100 y older than the building dates of the castles. This systemic effect corresponds to the age of wood used for lime burning and shall be accounted for when dating mortars using charcoals.